Controlled engineering of nano-sized FeOOH@ZnO hetero-structures on reduced graphene oxide for lithium-ion storage and photo-Fenton reaction. Issue 16 (3rd April 2020) - Xu, Binghui; Dai, Xin; Tan, Qingke; Wei, Yuan; Liu, Gonggang; Wu, Guanglei
Abstract : In this work, a nano-sized goethite and zinc oxide hetero-structure (FeOOH@ZnO) dispersed on reduced graphene oxide (RGO) sheets was synthesized for the first time to construct a ternary composite (FeOOH@ZnO/RGO) via a stepped graphene oxide (GO) deoxygenation process. Abstract : In this work, a nano-sized goethite and zinc oxide hetero-structure (FeOOH@ZnO) dispersed on reduced graphene oxide (RGO) sheets was synthesized for the first time to construct a ternary composite (FeOOH@ZnO/RGO) via a stepped graphene oxide (GO) deoxygenation process. Ferrous ions (Fe 2+ ) and metal Zn were employed as reducing agents, which were transformed into FeOOH and ZnO nanoparticles, respectively, to form a hetero-structure in the reaction. Particularly, the size of the nanoparticles could be controlled by limiting the growth kinetics in this work. As a result, a porous RGO architecture was constructed with well-dispersed hetero-structured nanoparticles consisting of encapsulated FeOOH and ZnO nanocrystals. The FeOOH@ZnO/RGO composite exhibited unique lithium-ion storage properties as an anode material for lithium-ion batteries. Also, compared with the binary FeOOH/RGO and ZnO/RGO composites, the ternary FeOOH@ZnO/RGO composite showed the best battery performance as an anode material for lithium-ion batteries and the best photo-Fenton degradation activity toward methylene blue (MB) degradation under simulated sunlight irradiation. The preparation route for the FeOOH@ZnO/RGO composite is straightforward, effective and has great potential to be scaled-up.